Respuesta :
-3x + 7x = -12
(-3 + 7)x = -12
4x = -12 (divide 4 from each side)
4x/4 = -12/4
x = -12/4
x = 3 <-answer
(-3 + 7)x = -12
4x = -12 (divide 4 from each side)
4x/4 = -12/4
x = -12/4
x = 3 <-answer
-3 + 7x = -12
First, simplify -3x + 7x to get 4x. / Your problem should look like: 4x = -12
Second, divide both sides by 4. / Your problem should look like: x = [tex]- \frac{12}{4} [/tex]
Third, simplify [tex] \frac{12}{4} [/tex] to 3. / Your problem should look like: x = -3
Answer: x = -3
First, simplify -3x + 7x to get 4x. / Your problem should look like: 4x = -12
Second, divide both sides by 4. / Your problem should look like: x = [tex]- \frac{12}{4} [/tex]
Third, simplify [tex] \frac{12}{4} [/tex] to 3. / Your problem should look like: x = -3
Answer: x = -3